Effects of dietary oyster peptide supplement on litter performance, immunological response of sows and growth performance of piglets - Tian, Xiaofeng; Wang, Jialu; Yao, Congcong; Shao, Muyang; Qi, Yatian; Gao, Zihao; Wang, Hongguo; Xia, Wei; Wang, Zhigang; Tao, Chenyu; Li, Junjie (Frontiers in Veterinary Science, 2025)
IntroductionAnimal breeding and reproduction techniques has led to an increase in the number of offspring of sows. However, weak piglets and low survival rate of piglets occurs frequently. During pregnancy, the late gestation is the most crucial period for fetal weight gain. Oyster peptides (OPI) are regarded as functional active substances derived from oysters with significant nutritional and medicinal value, exhibiting considerable potential for application. It remains unclear whether oyster peptides can play an important role in the field of sow reproduction. In this study, the objective was to investigate the impact of incorporating OPI into the diets of sows during the late gestation and lactation phases on litter performance, immunological response of sows and the growth and development of piglets.Methods100 sows were selected and were randomly divided into the control group (CON, basic diet) and the experimental group (OPI, supplemented with 2 mg/kg OPI in feed) with the feeding period from gestation day 90 to day 21 postpartum. First, litter performance, immunological response of sows and growth performance of piglets were analyzed; then, RNA-seq and q-PCR were used to detect the molecular mechanism of OPI.ResultsThe results demonstrated that the supplementation of OPI to the diets of sows in late gestation and lactation resulted in a significant increase in the number of healthy piglets and weaning survival rate (p ≤ 0.05); colostrum and placenta samples were collected during parturition, IgA, IgG and IgM in colostrum of sows also increased (p ≤ 0.05); expression levels of glucose transporter genes (GLUT4, SLC2A1), amino acid transporter genes (SNAT1, LAT1), and fatty acid transporter genes (FABP3) in the placenta were increased (p ≤ 0.05). The levels of pro-inflammatory factors (IL-1, IL-6, IL-8, AVPI1 were significantly decreased in the placenta, whereas the levels of anti-inflammatory factors (IL-10), antioxidant genes (SOD1, SOD2, GPX2, CAT), and anti-apoptotic genes (BCL2, BCL2L1) were sign.